In Defence of Progress. With an Appendix on Progress and Human enhancement. - Mäder, Denis (Momentum Quarterly, 2014)
The modern idea of progress assumes that time will bring a steady improvement in all things human. This idea was always a contested one. However, since the mid-20th century at the latest philosophical thought about progress has been almost exclusively critical. The present paper introduces the standard arguments of progress’s detractors, particularly the notion that progress should be understood dialectically as the transformation of good intentions into their opposite. It attempts to sketch a more timely conception of progress in opposition to this line of thought.